Availability and Utilization of Preschool Play Equipment - Saadu, Usman Tunde (ASEAN Journal of Educational Research and Technology, 2024)
This study investigates the availability and utilization of preschool play equipment. A descriptive survey research design was used. The population consists of 151 teachers, covering both private and public schools, according to the 2018/2019 Kwara Public Schools Census Report. The study sample was 108 preschool teachers from private and public schools in Ilorin West, Kwara State. A simple random sampling technique was used. Data collection was carried out using a research instrument entitled “Play Equipment Availability Checklist” (CAPE) and “Play Equipment Utilization Assessment Scale” (RUPE). The face and content validity of the instrument was determined by research supervisors and knowledgeable lecturers in the Department of Early Childhood Education and Basic Education. Restructuring and deletion of irrelevant items is done as necessary. Instrument reliability was determined by the test-retest method and Pearson Product Moment Correlation (PPMC) was used to compare the two sets of scores. Two hypotheses were tested at the 0.05 significance level. The findings show that school play equipment is available, while the utilization rate of preschool play equipment is very low. There were no significant differences in the availability or utilization of preschool play equipment by school type. Based on the research results, it is recommended that the government and the private sector provide play equipment to schools. In addition, the government should encourage the use of play equipment and ensure that teachers incorporate it into their teaching practice.